A Descriptive Analysis of the Board Characteristics and Financial Performance of the Romanian Companies Listed on the BSE - Bogdan Aurelian MIHAIL (Communications of International Proceedings, 2021)
The purpose of this paper is to provide a descriptive analysis of the board characteristics and performance variables of Romanian companies listed on the Bucharest Stock Exchange (BSE). Given the lack of public or private datasets on these variables, the paper compiled a large dataset for the 2019-2020 period. When compared to the summary statistics of the previous studies, the results show that the board characteristics have changed dramatically in the last decade. In particular, the proportion of independent and non-executive board members has increased significantly over the last decade, while the proportion of CEOs that hold a dual position (CEO and Chairman) has decreased. Furthermore, companies have been creating various board committees at an increasing rate.
Keywords: Corporate Governance; Board of Directors; Romania; Bucharest Stock Exchange; Board Independence; Board Committees.